Pesticide residue profiles, dietary risk assessment, and mitigation strategies in citrus production systems of Pakistan - Muneer Abbas; Akbar Hayat; Sohaib Afzaal; Muhammad Ghayoor Husnain; Hira Tariq; Fiaz Hussain; Niaz Hussain; Muhammad Saleem; Dilbar Hussain; Aleena Alam; Wang Dongze; Sohail Abbas (Food Control, 2026)

Genome sequencing reveals genes under selection for olfactory transduction in highland sheep - Anees Ahmad; Muhammad Ibrahim; Muhammad Yaqoob; Muhammad Fahim; Sher Hayat Khan; Israr Ud Din; Majid Khan; Sohail Ahmad (Molecular Genetics and Genomics, 2026)
Kutta is an indigenous sheep breed found in the mountainous region of Swat, Pakistan. In this study we evaluated the performance of Kutta sheep within their natural habitat and identified genomic regions associated with environmental adaptability using whole genome sequencing. Flocks are mostly managed under a transhumant production system with year-round breeding. Kutta sheep demonstrated higher lambing efficiency under the available resources. Although the body size of rams and ewes was comparable, significant variation was observed among different age groups. Whole genome sequencing identified 15.46 million variants relative to Oar_v1.0 reference genome assembly. Exonic variants accounted for 2.3% of all protein coding gene variants and affected 6347 genes. These genes were primarily enriched in pathways related to G protein-coupled receptor signaling (700 genes) and olfactory transduction (500 genes). Selective sweep analysis detected 1930 genes within the regions of high homozygosity across the genome. Based on homozygosity patterns, biological relevance, and colocalization with known QTLs, 11 candidate genes were identified as putative selective signature. Five of these genes (OR4C6L, OR1086L, OR5AK2L, QR5T2L, OR9Q2) belonged to the olfactory receptor family. These olfactory receptor genes may contribute to high-altitude adaptation in Kutta sheep by enhancing their ability to locate food resources, recognize mates, and detect predators in challenging mountainous environments. Further screening of the OR4C6L sequence across 12 indigenous sheep breeds revealed marked differences between highland and lowland populations. Collectively, these findings provide comprehensive genomic insights into high-altitude adaptation of sheep and highlight the potential role of olfactory perception in survival and environmental fitness.

Alternaria alternata: Mechanism of pathogenicity, host-interactions, and translational applications of pathogenicity research - Muhammad Sabir; Mansoor Hayat; Hasham Ahmad; Imdad Ullah; Zainab Shahbaz; Mobeen Abbas; Zhanbin Wang (Physiological and Molecular Plant Pathology, 2026)

Adsorption-coupled ozonation of real mariculture complex effluents' pharmaceuticals by lignocellulosic waste-based bimetallic biochar: Synergistic mechanism and implications - Muhammad Noman; Guangwei Yu; Wisal Ahmad; Wardah Hayat Khan (Journal of Water Process Engineering, 2026)

Retraction notice to ‘Hydrogeochemical properties, source provenance, distribution, and health risk of high fluoride groundwater: Geochemical control, and source apportionment’ [Environ. Pollut. 362, (2024) 125000] - Muhammad Ayub; Hira Javed; Abdur Rashid; Wardah Hayat Khan; Asif Javed; Tariq Sardar; Ghulam Mujtaba Shah; Ajaz Ahmad; Jörg Rinklebe; Parvaiz Ahmad (Environmental Pollution, 2026)

Climatic suitability and geospatial assessment of Black Soldier Fly Larvae (BSFL) for sustainable waste management - Muhammad Salam; Sami Ullah; Fakhri Alam; Camila Rodríguez-Ortega; Samia Elouali; Viola Vambol; Shafi'u Adamu; Viviana Bolletta; Faisal Hayat; Zhiyong Han (Environmental Development, 2026)

Engineered Adsorbents for Microplastic Mitigation: From Interfacial Mechanisms to Scalable Environmental Perspectives - Hammad Sajjad; Waleed Altaf; Ramika Javaid; Tehreem Fakhra; Muhammad Hayat; Ammar bin Yousaf; Nadeem Raza; Suryyia Manzoor; Lilia Basilio de Caland (Journal of Environmental Chemical Engineering, 2026)

Interannual variation in tree transpirational cooling and its controlling factors in warm-wet and hot-dry biomes - Muhammad Hayat; Liu Ran; Bai Jie; Xu Gui-Qing; Bilal Ahmad (Agricultural and Forest Meteorology, 2026)

Use selenium-doped TiO2 single-wall carbon nanotubes as promoter of biochemical indices in Solanum lycopersicum L. under bacterial wilt stress conditions - Asif Kamal; Akhtar Munir; Khizar Hayat Khan; Ulfat Ara; SK Safdar Hossain; Abdulrazak J. Otaru; Muhammad Tahir Amin; Hayat Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Plant growth-promoting rhizobacteria (PGPR) producing ACC deaminase and exopolysaccharides enhance salt tolerance in wheat - Mahnoor Hayat; Rashida Parveen; Muhammad Shoib Nawaz; Muhammad Ahmad Rao; Ahmed Waqar; Rubab Zahra. Naqvi; Munir Ahmad Anwar; Zahir Ahmad Zahir; Muhammad Qasim; M Ahmad Dogar; Tadeo Sáez Sandino; Brajesh K. Singh; et al. (World Journal of Microbiology and Biotechnology, 2026)

Radiological health risk assessment of natural radioactivity in Pakistan clay - Rabeea Abdul Jabbar; Amara Naseem; Muhammad Dilband; Syed Zafar Ilyas; Abdul Jabbar; Jahan Zeb; Khizar Hayat Satti (Environmental Monitoring and Assessment, 2026)

Field portable Cr2O3 nanozyme based paper sensors for on-site screening of arsenic and cadmium in quality control of herbal products - Fatima Yaseen; Muhammad Faizan; Ali Turab Jafry; Awn Muhammad; Akhtar Hayat; Huma Ajab (Food Bioscience, 2026)

Degree of coordination between above- and below-ground traits controls the establishment capability of two Haloxylon species in a dryland ecosystem - TuQiang Chen; GuiQing Xu; ShenSi Liu; Yan Li; Marcel C. Vaz; Muhammad Hayat (Flora, 2026)

Iron-Loaded Biochar Ameliorates Cadmium-Induced Phytotoxicity in Rapeseed by Modulating Cd Uptake, Nutrient Homeostasis, and Antioxidative Systems - Sumra Siddique Abbasi; Hafiz Saqib Hayat; Hua-Yi Chen; Muhammad Mohsin Altaf; Mudawi M. Nour; Afrah E. Mohammed (Journal of Soil Science and Plant Nutrition, 2026)

Peroxide crosslinking of UHMWPE using tea-polyphenols as anti-oxidants - Muhammad Aaqib Ishaq; Muhammad Kaleem Ullah Khalil; Qazi Muhammad Yaseen; Mohsin Hayat (Next Research, 2026)

A comparative analysis of crop water footprint, practices, and economic water productivity (EWP) in Punjab, Pakistan and Western Australia, Australia - Zohreh Rajabi; Stephen Gray; Shakeel Hayat; Muhammad Atiq Ur Rehman Tariq (Irrigation Science, 2026)
A comprehensive analysis of crop water footprint (WFP), water use efficiency (WUE) and economic water productivity (EWP) between 2010 and 2020 in two climatically and economically diverse agricultural regions: Punjab, Pakistan and Western Australia, Australia was undertaken. Using the Water Footprint Network method and climate, soil and agricultural production data, the study quantified green, blue and grey water footprints for five staple crops in each region. Normalization by local water scarcity and irrigation share was used to compare between the two regions with different water stress levels and irrigation dependence. Results showed that the total crop water requirements in Punjab increased by 12% during the study period due to changing climatic conditions. Cotton and rice had the highest WFP and dependence on irrigation, however generated relatively low economic returns per unit of water, showcasing inefficiency in the current agricultural system. In contrast, rain-fed crops in WA showed lower absolute crop water requirements and lower increases in normalized WFP, with stable WUE and EWP with cereals, showcasing efficient water use under climate-driven limitations. Normalization highlighted the difference in water stress, identifying that Punjab’s irrigation-intensive crops put much greater stress on local water resources than WA crops. Integration of biophysical and economic indicators, when normalizing for water scarcity, provides a strong basis to assess water practice of various agricultural systems. The results indicate the necessity for location-specific approaches: increased irrigation efficiency and suitable crop selection in Punjab; and climate-resilient cropping to maximize water use productivity and economic return in WA.

A comprehensive review of thermal ablation technologies for transdermal drug delivery: mechanisms, commercial products, and future smart systems - Muhammad Murtaza; Salman Ali Khan; Hayat Khan; SK Safdar Hossain (Drug Delivery and Translational Research, 2026)

Observation-based evidence reveals increased control of tree traits rather than hydroclimate on tree transpirational cooling across global regions - Muhammad Hayat; Liu Ran; Bai Jie; Xu Gui-Qing; Bilal Ahmad (Journal of Environmental Management, 2026)

Sodium cyclamate alters cardiac homeostasis via immunoinflammatory signaling modulation: A multi-biomarkers and in-silico evaluation - Muhammad Faisal Hayat; Abdulaziz Saleh Alkhoshaiban; Hesham M. Hassan; Syeda Sania Zahara; Ali Akbar; Khalid J. Alzahrani; Khalaf F. Alsharif; Fuad M. Alzahrani (Journal of Environmental Sciences, 2026)

Interactive effects of incubation and post-hatch lighting schedules on blood biochemistry and meat quality characteristics in Japanese quail - Hussnain Ali Akram; Jibran Hussain; Sohail Ahmad; Muhammad Hayat Jaspal (Tropical Animal Health and Production, 2026)

Retraction Note: Novel acetamide derivatives of 2-aminobenzimidazole prevent inflammatory arthritis in rats via suppression of pro-inflammatory mediators - Aymun Madni Zubair; Muhammad Nasir Hayat Malik; Waqas Younis; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Alamgeer Yuchi; Muhammad Naveed Mushtaq; Romeeza Tahir; Muhammad Bilal Sarwar; Muhammad Roman; Ayaz Ali Khan; et al. (Inflammopharmacology, 2026)

Nepetin attenuates sertraline-induced cardiac dysfunction by modulating notch signaling, oxidative stress, and inflammation: Echocardiographic and histological evidence - Hassan M. Otifi; Muhammad Faisal Hayat; Aqsa Bibi; Hesham M. Hassan; Ahmed Al-Emam (Tissue and Cell, 2026)

Machine learning-guided discovery of mitogen-activated protein kinase 7 (MAPK7 inhibitors): integrating virtual screening, docking, and molecular dynamics simulations - Chandni Hayat; Amar Ajmal; Nayab Gul; Muhammad Numan; Haleema Bibi; Naveed Akhtar; Laiba Sultan; Arif Ali; Muhammad Tahir Khan; Muhammad Saqib (In Silico Pharmacology, 2026)

Sulfoxaflor provokes progressive myocardial injury by disrupting HIF-1α/VEGFA signaling, redox balance, and inflammation: A comprehensive biochemical, echocardiographic, and histopathological approach - Yingying Dong; Salim Jamil; Mahmoud El Safadi; Ali Akbar; Muhammad Faisal Hayat; Ahmed Al-Emam; Hesham M. Hassan (Journal of Environmental Sciences, 2026)

Biochar and plant growth-promoting rhizobacteria: a promising combination enhancing wheat (Triticum aestivum L.) growth under chromium stress - Fazal Jalal; Awais Ahmad; Aqib Iqbal; Zafar Hayat Khan; Shah Fahad; Nazia Tahir; Fazal Said; Muhammad Imtiaz; Muhammad Ali Khan; Sayed Hussain; Attaur Rahman; Wasim Khan; et al. (Rhizosphere, 2025)

A review on seasonal variation and index-based assessment of heavy metal contamination in agricultural soils near Dhaka Export Processing Zone (DEPZ), Bangladesh - Md.Nahid Mahmud; Asif Ahmed; Shaila Sharmin; M.Rehan Dastagir; Muhammad Khizar Hayat; Gazi Faria Jahan Mim; Abdullah Al Kafi; Tasnim Tahara (Next Research, 2025)

Molybdenum induces hepatic impairments via dysregulating NLRP3, JAK1/STAT3 and NF-κB pathways: A dose dependent toxicity assessment - Mahmoud El Safadi; Abdulaziz Saleh Alkhoshaiban; Muhammad Faisal Hayat; Syeda Sania Zahara; Ali Akbar; Maha A. Al-Aream; Salim Jamil; Hesham M. Hassan (Journal of Trace Elements in Medicine and Biology, 2025)

Cardioprotective potential of azaleatin against sodium arsenite instigated sub-chronic cardiotoxicity via targeting TLR4/MyD88, JAK1/STAT3, and NF-κB in Sprague Dawley rats - Hesham M. Hassan; Aqsa Bibi; Muhammad Faisal Hayat; Khalid J. Alzahrani; Fuad M. Alzahrani; Meshari A. Alsuwat; Maha A. Al-Aream (Journal of Trace Elements in Medicine and Biology, 2025)

Therapeutic potential of spinacetin against cadmium-exacerbated hepatic ischemia/reperfusion injury via regulating AMPK/SIRT1/PGC-1α and NF-κB pathway - Aqsa Bibi; Hong-xing Zhang; Muhammad Faisal Hayat; Khalid J. Alzahrani; Khalaf F. Alsharif; Fuad M. Alzahrani (Journal of Trace Elements in Medicine and Biology, 2025)

Solid phase microextraction of chlorpyrifos residues in food samples using polyacrylamide@MOF/MXene composite - Sumaira Sabir; Nadeem Raza; Muhammad Hayat; Suryyia Manzoor; Faryal Aftab; Lilia Basilio de Caland; Muhammad Imran Khan; Ahmed Yar; Faisal K. Algethami; Mostafa E. Salem; Anis Ahmad Chaudhary; Muhammad Naeem Ashiq (Food Chemistry, 2025)

Interleukin-37 modulates microglial phenotype and inhibits inflammatory response via the MyD88/NF-κB pathway in lipopolysaccharide-induced neuroinflammation - Jingwen Zhang; Muhammad Abid Hayat; Yu Si; Tao Guo; Yinying Ni; Qian Wang; Yancheng Hong; Yudie Cao; Sijia He; Zijuan Weng; Fengmei Li; Hao Zuo; et al. (Inflammation Research, 2025)

Rice Husk Biochar and Alternate Wetting and Drying Irrigation Influence the Grain Yield and Water Productivity of Wet Direct‐Seeded Rice - Subesh Dhakal; Sheikh Faruk Ahmed; Deepranjan Sarkar; Hayat Ullah; Sushil Kumar Himanshu; Muhammad Yaseen; Suriyan Cha‐um; Avishek Datta (Irrigation and Drainage, 2025)
Biochar application and alternate wetting and drying (AWD) irrigation are promising practices for achieving cleaner rice production. This study evaluated the combined effects of biochar and AWD irrigation on the grain yield and water productivity (WP) of wet direct‐seeded rice (WDSR). A pot experiment combining five biochar doses (0, 5, 10, 15 and 20 t ha −1 ) with three soil water potential levels (0, −15 and −30 kPa) via AWD irrigation was conducted. Biochar at 20 t ha −1 significantly increased panicle number plant −1 (18%) and SPAD value (5%) compared with 0 t ha −1 biochar. The performance of the plants was similar between 0 and −15 kPa, whereas −30 kPa was stressful. Despite the reduced water input, −30 kPa resulted in 27% lower grain yield compared with 0 kPa at 0 t ha −1 . In contrast, −15 kPa did not cause notable growth or yield abnormalities. Moreover, 20 t ha −1 in combination with −15 kPa resulted in better crop performance, resulting in 86% greater root dry matter, 24% greater grain yield and 85% greater WP than those of the control. The results highlight the potential of the integrated application of biochar and AWD irrigation for enhancing the grain yield and WP of WDSR.

Faunistics of Syrphid flies (Diptera: Syrphidae) from Chakesar Valley, District Shangla, Pakistan and their biogeographic association - Waqas Ahmad; Jalal Hayat Khan; Qudrat Ullah; Khalid khan; Muhammad Zubair; Sumara Aslam; Muhammad Qasim; Muhammad Ather Rafi (International Journal of Tropical Insect Science, 2025)

Neuroprotective potential of fortunellin against titanium dioxide nanoparticles induced neurotoxicity via regulating NLRP3, HMGB1/RAGE, and NF-κB pathway: A biochemical, histological and in-silico experimentation - Abdulaziz Saleh Alkhoshaiban; Muhammad Faisal Hayat; Mahmoud El Safadi; Hesham M. Hassan; Ali Akbar; Syeda Sania Zahara; Ahmed Al-Emam (Toxicon, 2025)

Casuarinin modulates renin-angiotensin-aldosterone system to counter ephedrine-induced myocardial damage in rats - Hesham M. Hassan; Muhammad Faisal Hayat; Ali Akbar; Azka Zafar; Khalid J. Alzahrani; Fuad M. Alzahrani; Abrar Aljohani (Toxicon, 2025)

A machine learning assisted approach to classify rose species and varieties with laser induced breakdown spectroscopy - Maryam Manzoor; Muhammad Faheem; Muhammad Nadeem; Guljan Shreen; Faisal Hayat; Adnan Younis; Yasir Jamil (Analytica Chimica Acta, 2025)

Syringetin ameliorates thallium sulphate induced renal dysfunction via regulating Nrf2/Keap-1, TLR4/HMGB1/RAGE and NF-κB pathway - Hassan M. Otifi; Muhammad Faisal Hayat; Ali Akbar; Syeda Sania Zahara; Khalid J. Alzahrani; Fuad M. Alzahrani; Khalaf F. Alsharif (Tissue and Cell, 2025)

Pinobanksin ameliorates perfluorooctane sulfonate-evoked cardiotoxicity via targeting Nrf-2/Keap-1, oxidative damage and inflammation in Sprague Dawley rats - Maryam Javed; Quratulann Sattar; Muhammad Faisal Hayat; Hamida Hamdi; Muhammad Zaid Salar (Tissue and Cell, 2025)

Effect of erucic acid against DMBA-induced breast cancer via inflammatory/apoptosis pathway - Abdulaziz Alamri; Fahad A. Al-Abbasi; Muhammad Afzal; May M. Alqurashi; Thamir M. Eid; Hayat M. Albishi; Ehssan Moglad; Nadeem Sayyed; Imran Kazmi (Food Bioscience, 2025)

Image segmentation and machine learning modelling for water status determination and precision irrigation management - Hamza Salah Ud Din; Aqib Iqbal; Fazal Jalal; Awais Ahmad; Muhammad Haris Paracha; Shah Fahad; Zafar Hayat Khan; Shah Saud; Taufiq Nawaz (Journal of Crop Science and Biotechnology, 2025)

Foliar Application of Silicon Alleviates Drought Stress in Chickpea (Cicer arietinum L.) by Improving Growth, Photosynthetic and Antioxidant Metabolism - Muhammad Faizan Ali; Mukhtar Ahmed; Laiba Mukhtar; Nadir Ali; Ghulam Qadir; Rifat Hayat; Shakeel Ahmad (Journal of Soil Science and Plant Nutrition, 2025)

Impact Analysis of Climate Change, Socioeconomic Development, and Hydropower Generation on Water Availability in the Chitral River Basin Using Water Evaluation and Planning (WEAP) Model - Bushra Zaman; Muhammad Atiq Ur Rehman Tariq; Abdullah Nadeem; Muhammad Kaleem Sarwar; Muhammad Waseem; Mudassar Iqbal; Shakeel Hayat; Khalil Ahmed; Muhammad Usman (Water Conservation Science and Engineering, 2025)
Water, energy, and food are three major issues of concern because of the rapid growth of the population and economy, which are exacerbated by climate change. The disparity between the availability and demand of water is largely driven by domestic and agricultural uses, and it is important to evaluate its impact on hydropower generation. This study aims to integrate climate change, socioeconomic development, and hydropower generation analysis using the water evaluation and planning model (WEAP). This study uses the CMIP6 model to make future projections under shared socioeconomic pathways (SSPs). This study examined the projections of water demand under different scenarios (SSP1-2.6, SSP2-4.5, and SSP5-8.5) using the MPI-ESM1-2HR climate change model. In the reference year 2000, domestic water demand stood at 15 MCM, escalating to 54 MCM under the SSP5-8.5 scenario. Concurrently, agricultural water demand, which was 93.72 MCM in 2000, is projected to surge to 197.35 MCM by 2050. Based on expected future changes in streamflow, the results show that Golen Gol’s hydropower potential varies with the effects of socioeconomic and climatic changes. However, the fluctuation in hydropower generation is more prominent during June and July, leading to an increase in hydropower in future scenarios. The study findings suggest that by 2050, the combination of population growth and agricultural expansion will substantially escalate water demand, posing risks to both the environment and human populations. Consequently, adopting enhanced irrigation methods, refining agricultural techniques, and erecting water conservation and retention infrastructures could effectively mitigate these challenges. To formulate sustainable water management strategies, it is advised to further utilize the integrated water–energy–food nexus approach, strengthened by merging WEAP with the energy modeling program Low Emissions Analysis Platform (LEAP) for hydropower generation.

Jasmonic Acid as a Regulator in Plant Stress Tolerance: Mechanisms and Agricultural Implications - Jalil Ahmad; Faisal Hayat; Ummara Khan; Muhammad Ahsan Altaf; Muhammad Ahmad; Muhammad Tahir Akram; Karthishwaran Kandhan; Mohamed S. Sheteiwy; Juan Li; Mohammed Alyafei (Journal of Crop Health, 2025)

Efficacy of Flumetsulam for Post-Emergence Weed Management in Chickpea (Cicer Arietinum L.) Under the Semi-Arid Region of Pakistan - Muhammad Khuram Razzaq; Ali Aziz; Faisal Hayat; Muhammad Zia Ul Haq; Irfan Rasool; Muhammad Naveed Babur; Ali Aslam; Sher Muhammad; Ammara Tahir; Khalid Hussain (Journal of Crop Health, 2025)

Effect of Aloe Vera-Based Coating on Physicochemical and Phytochemical Properties of Wild Apricot Variety - Nazish Ashraf; Imran Hayat; Nagina Rafique; Khawaja Shafique Ahmad; Muhammad Zubair Khan; Khalid J. Alzahrani; Khalaf F. Alsharif (Applied Fruit Science, 2025)

A host availability-driven model for predicting the distribution of Red Palm Weevil in China - Umer Hayat; Muhammad Hammad Ahmad; Waqar Sattar; Ziying Zhu (Crop Protection, 2025)

Enhanced apoptosis in damaged laminar tissue of acute laminitis induced by oligofructose overload in dairy cows - Muhammad Abid Hayat; Jiafeng Ding; Xianhao Zhang; Tao Liu; Jiantao Zhang; Hong Bin Wang (Veterinary Immunology and Immunopathology, 2025)

Pharmacotherapeutic role of astringin against chromium induced nephrotoxicity via modulating TLR4/MyD88, HMGB1/RAGE and NF-κB pathway: A biochemical and pharmacokinetic approach - Han Hu; Muhammad Faisal Hayat; Syeda Sania Zahara; Ali Akbar; Khalid J. Alzahrani; Khalaf F. Alsharif; Fuad M. Alzahrani; Ahmed Al-Emam (Journal of Trace Elements in Medicine and Biology, 2025)

Sorbitol induces sub-chronic nephrotoxicity via escalating JAK1/STAT3, oxidative stress and inflammation in Sprague Dawley rats - Fuad M. Alzahrani; Aqsa Bibi; Muhammad Faisal Hayat; Khalid J. Alzahrani; Khalaf F. Alsharif; Adnan Ali (Food and Chemical Toxicology, 2025)

Elaidic acid induces testicular oxidative stress, inflammation, Wnt/β-catenin disruption and abnormalities in steroidogenesis, spermatogenesis and histo-architecture in Sprague Dawley rats - Fuad M. Alzahrani; Muhammad Faisal Hayat; Ali Akbar; Syeda Sania Zahara; Meshari A. Alsuwat; Khalid J. Alzahrani; Ahmed Al-Emam (Food and Chemical Toxicology, 2025)

Tailoring g-C3N4 properties through P and K co-doping: advancing photocatalytic CO2 reduction to CH4 - Ahmed Ismail; Muhammad Zahid; Bilal Ahmad; Salman Hayat; Sher Ali; Syed ul Hasnain Bakhtiar; Abdullah N. Alodhayb; Xiaoqiang Wu; Qaisar Alam; Sharafat Ali; Liang Qiao (Chemical Engineering Journal, 2025)

Mitigation Potential of Green-Zinc Oxide Nanoparticles for Nickel (Ni) Stress in Watermelon Plants: Regulation of Cellular Oxidative Stress Metabolism and Reduction in Ni Translocation - Ahlam Khalofah; Muhammad Qaisar Naeem Khan; Hafiz Saqib Hayat (Journal of Soil Science and Plant Nutrition, 2025)

Investigating the Role of Gibberellic Acid in Fruit Drop Mitigation and Fruit Quality Improvement in Date Palm Cultivars - Hammad Hussain; Yue Yu; Abdul Haseeb Ahmed; Faisal Hayat; Muhammad Awais; Abdullah Ma’Arij; Guo Wei; Rashad Qadri (Applied Fruit Science, 2025)

Leveraging industry 4.0 technologies and industrial symbiosis: Advancing circular economy practices in BRICS economies - Muhammad Uzair Ali; Itbar khan; Hayat khan (Journal of Environmental Management, 2025)

Palliative potential of genistein to counteract endosulfan instigated colon toxicity via regulating TLR4/MyD88, JAK1/STAT3 and NF-κB pathway: A biochemical and histological approach - Khalid J. Alzahrani; Mahmoud El Safadi; Khalaf F. Alsharif; Fuad M. Alzahrani; Muhammad Faisal Hayat (Tissue and Cell, 2025)

Afzelechin alleviates deltamethrin induced hepatic dysfunction via regulating TLR4/MyD88, HMGB1/RAGE and NF-κB pathway - Fuad M. Alzahrani; Khalid J. Alzahrani; Khalaf F. Alsharif; Muhammad Faisal Hayat; Ahmed Al-Emam (Toxicology and Applied Pharmacology, 2025)

Efficacy of ascorbic acid coated quantum dots in alleviating lead-induced oxidative damage and enhancing growth parameters in rice (Oryza sativa L.) for sustainable cultivation - Aliza Falak; Muhammad Anas; Amjid Khan; Alvina Hayat; Zeenat Shaheen; Muhammad Hamzah Saleem; Shah Fahad; Umar Masood Quraishi (Journal of Trace Elements in Medicine and Biology, 2025)

Diagenetic and mineralogical impacts on clastic reservoir; A case study from the lower Indus Basin, Pakistan - Muhammad Nofal Munir; Mohammad Zafar; Muhsan Ehsan; Rujun Chen; Kamal Abdelrahman; Jar Ullah; Tassawar Hayat; Hamad Ur Rahim (Journal of Asian Earth Sciences, 2025)

Maize cultivar mixtures: a sustainable approach for weed management under reduced herbicide dose - Amina Shahbaz; Gul Zaib Hassan; Muhammad Zia Ul Haq; Saira Shafiq; Amar Matloob; Rizwan Maqbool; Muhammad Tayyab Hanif; Muhammad Abu Bakar Hayat (Phytoparasitica, 2025)

Novel mutations in exon 2 of follistatin (FST) gene associated with wool fiber diameter in sheep - Tahira Mir; Muhammad Ibrahim; Muhammad Siraj; Sajid Ali Khan Bangash; Sher Hayat Khan; Majid Khan; Muhammad Tayyab; Sohail Ahmad (Small Ruminant Research, 2025)

Amine-functionalized organically modified silica for the effective adsorption of Chlorpyrifos and Triazophos Residues from Orange juice - Muhammad Hayat; Suryyia Manzoor; Nadeem Raza; Hina Raza; Ayesha Javid; Zeeshan Ali; Muhammad Imran Khan; Faisal K. Algethami; Najla AlMasoud; Taghrid S. Alomar (Food Chemistry, 2025)

Combined pharmacological and computational approaches unraveling the protective effects of Cassia angustifolia extract against NANO2 - induced neurodegeneration and hepatotoxicity - Shabina Ishtiaq Ahmed; Humaira Ismatullah; Qaisar Mansoor; Muhammad Yaseen; Aisha Naveed; Muhammad Qasim Hayat; Saadia Zahid; Junaid Arshad; Mubarra Tahir; Mashooq Ahmad Bhat (Food Bioscience, 2025)

Systematic review on buparvaquone resistance associated with non-synonymous mutation in drug binding genes site of Theileria annulate - Muhammad Rashid; Muhammad Hassan Hayat; Naveed Zahra; Mian Sayed Khan; Suleman; Muhammad Nadeem; Tauseef ur Rehman; Muhammad Ehsan; Muhammad Irfan Malik; Muhammad Kashif Obaid; Amir Bakhsh; Mohamed Aziz Darghouth; et al. (Veterinary Parasitology, 2024)

Pharmacotherapeutic potential of bilobetin to combat chromium induced hepatotoxicity via regulating TLR-4, Nrf-2/Keap-1, JAK1/STAT3 and NF-κB pathway: A pharmacokinetic and molecular dynamic approach - Mahmoud El Safadi; Muhammad Faisal Hayat; Ali Akbar; Abdullah Nisar; Fuad M. Alzahrani; Khalid J. Alzahrani (Journal of Trace Elements in Medicine and Biology, 2024)

Exploring the role of the microbiome of the H. illucens (black soldier fly) for microbial synergy in optimizing black soldier fly rearing and subsequent applications - Muhammad Salam; Viviana Bolletta; Ying Meng; Wael Yakti; Valentina Grossule; Dezhi Shi; Faisal Hayat (Environmental Pollution, 2024)

RETRACTED: Hydrogeochemical properties, source provenance, distribution, and health risk of high fluoride groundwater: Geochemical control, and source apportionment - Muhammad Ayub; Hira Javed; Abdur Rashid; Wardah Hayat Khan; Asif Javed; Tariq Sardar; Ghulam Mujtaba Shah; Ajaz Ahmad; Jörg Rinklebe; Parvaiz Ahmad (Environmental Pollution, 2024)

Interactive use of biochar and chemical fertilizer for improving nutrient availability and crop growth in rainfed area - Saddam Hussain; Rifat Hayat; Saleem Ullah; Muhammad Ashraf; Rebwar Nasir Dara; Muhammad Adeel Ashraf; Sami Ullah Khan; Muyassar Norberdiyeva; Manish Gupta; M. Ijaz Khan (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)

Diagnostic study on extreme precipitation over Karachi during August 2020 - Amna Bibi; Shahzada Adnan; Muhammad Latif; Azmat Hayat Khan; Anjum Nazir Zaighum; Kalim Ullah (Meteorology and Atmospheric Physics, 2024)

Citric acid-driven cadmium uptake and growth promotion mechanisms in Brassica napus - Saiqa Menhas; Kashif Hayat; Daohui Lin; Muhammad Shahid; Jochen Bundschuh; Saiyong Zhu; Sikandar Hayat; Weiping Liu (Chemosphere, 2024)

Turning trash into Treasure: Extracting precious metals from e-waste with Electrochemically Exfoliated graphene derivatives - Mamoona Hayat; Muhammad Waseem; Saira Arif; Junaid Ali; Abdul Sattar; Sobia Dilpazir; Khadim Hussain; Lubna Tabassam (Chemical Engineering Journal, 2024)

Impact of Drought Duration and Severity on Drought Recovery Period for Different Land Cover Types in Balochistan, Pakistan - Hayat Ullah Khan; Muhammad Waseem; Mudassar Iqbal; Faraz Ul Haq; Abu Bakar Arshed; Muhammad Laraib; Umar Sultan (Journal of the Indian Society of Remote Sensing, 2024)

Influence of flaxseed-derived diglyceride-based high internal phase Pickering emulsions on the rheological and physicochemical properties of myofibrillar protein gels - Iftikhar Hussain Badar; Ziyi Wang; Yafei Zhou; Muhammad Hayat Jaspal; Haotian Liu; Qian Chen; Baohua Kong (Food Chemistry, 2024)

Retraction Note: Novel mannich-based derivative of 2-mercaptobenzimidazole (AK7): a new candidate for the treatment of inflammatory arthritis owing to its NF-κB1 inhibitory potential - Gagun Kamran; Hafiz Amir Ali Kharl; Muhammad Nasir Hayat Malik; Waqas Younis; Humaira Nadeem; Aymun Madni Zubair; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Ramla Shabbir; Asma Akram; Irfan Anjum; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Ameliorative potential of eriocitrin against cadmium instigated hepatotoxicity in rats via regulating Nrf2/keap1 pathway - Muhammad Faisal Hayat; Muhammad Zohaib; Muhammad Umar Ijaz; Moazama Batool; Asma Ashraf; Bader O. Almutairi; Usman Atique (Journal of Trace Elements in Medicine and Biology, 2024)

Effect of flaxseed-derived diglyceride-based high internal phase Pickering emulsion on the quality characteristics of reformulated beef burgers - Iftikhar Hussain Badar; Ziyi Wang; Yafei Zhou; Xiang Guo; Muhammad Hayat Jaspal; Baohua Kong; Haotian Liu (Meat Science, 2024)

Which bioenergy with carbon capture and storage (BECCS) pathways can provide net-negative emissions? - Muhammad Adnan Hayat; Khalid Alhadhrami; Amro M. Elshurafa (International Journal of Greenhouse Gas Control, 2024)

Salicylic Acid-Induced Antioxidant Defense System Alleviates Cadmium Toxicity in Wheat - Umer Hayat; Kaleem ul din; Arslan Haider; Tahrim Ramzan; Bilal Ahmad Shahzad; Muhammad Ahmad; Usman Zulfiqar; Muhammad Faisal Maqsood; Sadam Hussain; Mona S. Alwahibi; Mohamed S. Elshikh (Journal of Soil Science and Plant Nutrition, 2024)

The chemical composition and biological activities of plant essential oils against Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) - Nimra Altaf; Muhammad Irfan Ullah; Muhammad Arshad; Muhammad Afzal; Laila A. Al‑Shuraym; Naunain Mehmood; Zafar Hayat; Samy M. Sayed (Journal of Plant Diseases and Protection, 2024)

Examining drinking water quality: analysis of physico-chemical properties and bacterial contamination with health implications for Shangla district, Khyber Pakhtunkhwa, Pakistan - Muhammad Salam; Dong Bo; Fakhri Alam; Islam Uddin; Md. Nuralam Hossain; Faisal Hayat; Waheed Ullah (Environmental Geochemistry and Health, 2024)

Isolation and characterization of novel cadmium-resistant Escherichia fergusonii ZSF-15 from industrial effluent for flocculant production and antioxidant enzyme activity - Saima Zafar; Asma Ashraf; Sumreen Hayat; Muhammad Hussnain Siddique; Muhammad Waseem; Mudassir Hassan; Hira Qaisar; Saima Muzammil (Environmental Monitoring and Assessment, 2024)

Empirical linkages among financial development, digital infrastructure, energy transition and natural resources footprints in BRICS region - Fang Hou; Muhammad Amir Khan; Malik Tahir Hayat (Resources Policy, 2024)

Comparative morpho-physiological traits, antioxidant defense and nutritional profiling under Cd stress of japonica-indica elite rice (Oryza sativa L.) cultivars - Alvina Hayat; Muhammad Anas; Zeenat Shaheen; Aliza Falak; Umar Masood Quraishi (Journal of Crop Science and Biotechnology, 2024)

Efficient performance of InP and InP/ZnS quantum dots for photocatalytic degradation of toxic aquatic pollutants - Maryam Abbasi; Rukhsanda Aziz; Muhammad Tariq Rafiq; Aziz Ur Rahim Bacha; Zahid Ullah; Abdul Ghaffar; Ghulam Mustafa; Iqra Nabi; Malik Tahir Hayat (Environmental Science and Pollution Research, 2024)

Dynamic impact of demographic features, FDI, and technological innovations on ecological footprint: evidence from European emerging economies - Florian Nuta; Muhammad Shahbaz; Itbar Khan; Ibrahim Cutcu; Hayat Khan; Mehmet Vahit Eren (Environmental Science and Pollution Research, 2024)

Impact of Various Combinations of Organic and Inorganic Fertilizers on Fruit Production and Quality of ‘Kinnow’ Mandarin (Citrus reticulata Blanco.) - Muhammad Asim; Faisal Hayat; Tehseen Ashraf; Fakhara Khanum; Juan Li; Yang Peng; Yanxiao Ma; Shahid Iqbal; Ummara Khan; Sitwat Riaz; Panfeng Tu; Fiaz Hussain; et al. (Applied Fruit Science, 2024)

Melatonin supplementation alleviates drought stress in peach (Prunus persica) seedlings by improving photosynthesis, root morphological traits, and antioxidant defense system - Shahid Iqbal; Faisal Hayat; Mujahid Hussain; Naveed Mushtaq; Muneer Rehman; Alaiha Asif; Ummara Khan; Muhammad Adnan Shahid (Acta Physiologiae Plantarum, 2024)

Amentoflavone mediated hepatoprotection to counteract paraquat instigated hepatotoxicity via modulating Nrf2/keap1 pathway: A biochemical, inflammatory, apoptotic and histopathological study - Muhammad Umar Ijaz; Naila Ghafoor; Muhammad Faisal Hayat; Bader O. Almutairi; Usman Atique (Pesticide Biochemistry and Physiology, 2024)

A holistic approach to embracing the United Nation's Sustainable Development Goal (SDG-6) towards water security in Pakistan - Ghulam Mujtaba; Mansoor Ul Hassan Shah; Abdul Hai; Muhammad Daud; Mazhar Hayat (Journal of Water Process Engineering, 2024)

Advances/Scope and prospects of g-C3N4 derived fascinating photocatalyst as a leading route towards solar energy adaption - Asif Hayat; Muhammad Sohail; Zeeshan Ajmal; Hala H. Abd El-Gawad; Djamel Ghernaout; Yas Al-Hadeethi; Saleem Raza; Yasin Orooji (Journal of Cleaner Production, 2024)

Magnetic solid phase extraction of aminoglycosides residue in chicken egg samples using Fe3O4-GO-Agarose-Chitosan composite - Muhammad Sajjad; Rasmiah Almufarij; Zeeshan Ali; Muhammad Sajid; Nadeem Raza; Suryyia Manzoor; Muhammad Hayat; Ehab A. Abdelrahman (Food Chemistry, 2024)

Comparative taxonomy and evolutionary significance of foliar epidermis in Jasminum L. (Oleaceae) based on light and scanning electron microscopy - Naeem Akhtar; Muhammad Q. Hayat; Umer Habib; Muhammad A. Khan; Saad I. Malik; Hina Hafeez; Adil Hussain; Azhar Hussain; Daniel Potter (Flora, 2024)

New insights in improving sustainability in meat production: opportunities and challenges - Pavan Kumar; Abubakar Ahmed Abubakar; Akhilesh Kumar Verma; Pramila Umaraw; Muideen Adewale Ahmed; Nitin Mehta; Muhammad Nizam Hayat; Ubedullah Kaka; Awis Qurni Sazili (Critical Reviews in Food Science and Nutrition, 2023)

Unraveling the mechanisms of cadmium toxicity in horticultural plants: Implications for plant health - Muhammad Ahsan Altaf; Safina Naz; Ravinder Kumar; Hasan Sardar; Muhammad Azher Nawaz; Awadhesh Kumar; Priyanka Lal; Riaz Ahmad; Faisal Hayat; Muneeb Ahmad Wani; Rahul Kumar Tiwari; Milan Kumar Lal (South African Journal of Botany, 2023)

Current understanding of boosting power of salicylic acid for abiotic stress tolerance in horticultural crops - Muhammad Ahsan Altaf; Rabia Shahid; Priyanka Lal; Riaz Ahmad; Faisal Zulfiqar; Awadhesh Kumar; Faisal Hayat; Ravinder Kumar; Milan Kumar Lal; Safina Naz; Rahul Kumar Tiwari (South African Journal of Botany, 2023)

Abiogenic silicon: Interaction with potentially toxic elements and its ecological significance in soil and plant systems - Babar Hussain; Luqman Riaz; Kun Li; Kashif Hayat; Naveed Akbar; Muhammad Zakwan Hadeed; Bowei Zhu; Shengyan Pu (Environmental Pollution, 2023)

Annual effective dose estimation of radon in drinking water sources of Nizampur basin, North Western Pakistan - Jehangir Ijaz; Wajid Ali; Said Muhammad; Hayat Ullah; Danish Ather; Imran Ud Din (Isotopes in Environmental and Health Studies, 2023)

Exploring the electrochemical properties of CuSe-decorated NiSe2 nanocubes for battery-supercapacitor hybrid devices - Mudassir Hayat; Yuxue Zhou; Muhammad Zia Ullah Shah; Muhammad Sana ullah; Muhammad Bilal Hanif; Hongying Hou; Umar Arif; Shaukat Khan; Ahmed M. Hassan; Ammar M. Tighezza; Muhammad Sajjad; Raghavender Vadla (Chemosphere, 2023)

Biogas Energy Resources in Pakistan Status, Potential, and Barriers - Muhammad Wakeel; Tasawer Hayat; Noor Samad Shah; Jibran Iqbal; Zia Ul Haq Khan; Ghulam Mustafa Shah; Atta Rasool (Utilities Policy, 2023)

Effects of micro(nano)plastics on soil nutrient cycling: State of the knowledge - Muhammad Salam; Huaili Zheng; Yingying Liu; Aneeqa Zaib; Syed Aziz Ur Rehman; Nimra Riaz; Moataz Eliw; Faisal Hayat; Hong Li; Fayuan Wang (Journal of Environmental Management, 2023)

Paper based colorimetric sensor using novel green magnetized nanocomposite of pinus for hydrogen peroxide detection in water and milk - Mehrosh Buzdar; Asim Yaqub; Akhtar Hayat; Muhammad Zia Ul Haq; Aizaz Khan; Huma Ajab (Food Bioscience, 2023)

Impact of graded levels of coated calcium butyrate on growth performance and serological indices during pre-weaning stage in Holstein calves - Abdur Rahman; Muhammad Furhan Arshad; Shah Nawaz; Zafar Hayat; Syed Ehtisham ul Haque; Saima Saima; Akhtar Rasool Asif; Muawuz Ijaz; Muhammad Zeeshan Anwar (Tropical Animal Health and Production, 2023)

Genome-wide analysis and expression profiling of YUCCA gene family associated with plant vigor in Japanese apricot (prunus mume Sieb. Et zucc) - Faisal Hayat; Yang Bai; Shahid Iqbal; Chengdong Ma; Muhammad Moaaz Ali; Muhammad Adnan Shahid; Mahmood Ul Hasan; Walid F. A. Mosa; Ummara Khan; Huang Xiao; Zhihong Gao (Horticulture, Environment, and Biotechnology, 2023)

Revolutionizing Chronic Obstructive Pulmonary Disease Care with the Open AI Application: ChatGPT - Muhammad Hasnain; Asad Hayat; Akbar Hussain (Annals of Biomedical Engineering, 2023)

Pleiotropic melatonin-mediated responses on growth and cadmium phytoextraction of Brassica napus: A bioecological trial for enhancing phytoremediation of soil cadmium - Saiqa Menhas; Xijia Yang; Kashif Hayat; Jochen Bundschuh; Xunfeng Chen; Nan Hui; Dan Zhang; Shaohua Chu; Yuanfei Zhou; Esmat F. Ali; Muhammad Shahid; Jörg Rinklebe; et al. (Journal of Hazardous Materials, 2023)

Engineering legumes for drought stress tolerance: Constraints, accomplishments, and future prospects - Arshad Jalal; Kamran Rauf; Babar Iqbal; Rabia Khalil; Hayat Mustafa; Muhammad Murad; Farhan Khalil; Sulaiman Khan; Carlos Eduardo da Silva Oliveira; Marcelo Carvalho Minhoto Teixeira Filho (South African Journal of Botany, 2023)

High temporal and spatial resolution characteristics of evaporation, transpiration, and evapotranspiration from a subalpine wetland by an advanced UAV technology - Chunhua Yan; Jiao Xiang; Longjun Qin; Bei Wang; Zhe Shi; Weiyang Xiao; Muhammad Hayat; Guo Yu Qiu (Journal of Hydrology, 2023)

Radiological risk assessment from the Gamma spectrometry of soil samples in the vicinity of a research centre in Nilore, Pakistan - Tahira Shabbir; Muhammad Sohail; Rizwan Ahmed; Masroor Ahmad; Khizar Hayat Satti (Environmental Monitoring and Assessment, 2023)

The role of green finance in mitigating environmental degradation: Empirical evidence and policy implications from complex economies - Umar Numan; Benjiang Ma; Muhammad Sadiq; Hayat Dino Bedru; Can Jiang (Journal of Cleaner Production, 2023)

Molecularly imprinted ormosil as a sorbent for targeted dispersive solid phase micro extraction of pyriproxyfen from strawberry samples - Muhammad Hayat; Suryyia Manzoor; Hina Raza; Muhammad Imran Khan; Abdallah Shanableh; Muhammad Sajid; Tahani Mazyad Almutairi; Rafael Luque (Chemosphere, 2023)

Effects of prepartum melatonin treatment and suckling on postpartum reproductive performance of Beetal goats under subtropical conditions - Muhammad Afzaal; Muhammad Irfan-ur-Rehman Khan; Waqas Ahmad; Amir Hayat; Qasir Abbas; Muhammad Arshad; Nasir Hameed; Imran Mohsin; Amjad Riaz (Small Ruminant Research, 2023)

RETRACTED ARTICLE: Novel mannich-based derivative of 2-mercaptobenzimidazole (AK7): a new candidate for the treatment of inflammatory arthritis owing to its NF-κB1 inhibitory potential - Gagun Kamran; Hafiz Amir Ali Kharl; Muhammad Nasir Hayat Malik; Waqas Younis; Humaira Nadeem; Aymun Madni Zubair; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Ramla Shabbir; Asma Akram; Irfan Anjum; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Mining therapeutic targets from the antibiotic-resistant Campylobacter coli and virtual screening of natural product inhibitors against its riboflavin synthase - Khurshid Jalal; Kanwal Khan; Ajmal Hayat; Diyar Ahmad; Ghallab Alotaibi; Reaz Uddin; Mutaib M. Mashraqi; Ahmad Alzamami; Muhammad Aurongzeb; Zarrin Basharat (Molecular Diversity, 2023)

Improving animal welfare status and meat quality through assessment of stress biomarkers: A critical review - Pavan Kumar; Muideen Adewale Ahmed; Abubakar Ahmed Abubakar; Muhammad Nizam Hayat; Ubedullah Kaka; Mokrish Ajat; Yong Meng Goh; Awis Qurni Sazili (Meat Science, 2023)

Algae extract delamination of molybdenum disulfide and surface modification with glycidyl methacrylate and polyaniline for the elimination of metal ions from wastewater - Saleem Raza; Muhammad Usman Hameed; Ehsan Ghasali; Asif Hayat; Yasin Orooji; Hongjun Lin; Ceren Karaman; Fatemeh Karimi; Nevin Erk (Environmental Research, 2023)

Assessment of corium concrete interaction and impact of water ingression mechanism using top flooding strategy for a small PWR with MELCOR 2.2 - Nasir Hayat Hengra; Chang Hyun Song; Sung Joong Kim; Muhammad Ilyas (Annals of Nuclear Energy, 2023)

Assessing the variations of evapotranspiration and its environmental controls over a subalpine wetland valley in China - Jiao Xiang; Muhammad Hayat; Guo Yu Qiu; Weiyang Xiao; Xianli Xu; Peng Mao; Chunhua Yan; Longjun Qin (Journal of Hydrology, 2023)

Comparative genomics with evolutionary lineage in Streptomyces bacteria reveals high biosynthetic potentials - Khorshed Alam; Md. Mahmudul Islam; Saiful Islam; Jinfang Hao; Muhammad Nazeer Abbasi; Muhammad Hayat; Muhammad Shoaib; Youming Zhang; Aiying Li (World Journal of Microbiology and Biotechnology, 2023)

Prospects of antimicrobial peptides as an alternative to chemical preservatives for food safety - Iqra Kamal; Usman Ali Ashfaq; Sumreen Hayat; Bilal Aslam; Muhammad Hassan Sarfraz; Hamna Yaseen; Muhammad Shahid Riaz Rajoka; Asad Ali Shah; Mohsin Khurshid (Biotechnology Letters, 2023)

Determining effect of tree on wheat growth and yield parameters at three tree-base distances in wheat/Jand (Prosopis cineraria) agroforestry systems - A. Khan; G. Ali Bajwa; X. Yang; M. Hayat; J. Muhammad; F. Ali; A. Quddoos; M. Amin; T. Ullah Khan; A. Ullah Khan (Agroforestry Systems, 2023)

Pre-slaughter stress mitigation in goats: Prospects and challenges - Pavan Kumar; Abubakar Ahmed Abubakar; Muideen Adewale Ahmed; Muhammad Nizam Hayat; Ubedullah Kaka; Mirian Pateiro; Awis Qurni Sazili; Louwrens C. Hoffman; Jose M. Lorenzo (Meat Science, 2023)

Does location of the households’ matters? Identifying the households’ willingness to pay and preference heterogeneity in advancement of vulnerable ecosystem services: An approach of choice experiment - Muhammad Abu Sufyan Ali; Zhihe Zhang; Sufyan Ullah Khan; Arshad Ahmad Khan; Mohammad Musa; Preethu Rahman; Yousaf Hayat (Environmental Science and Pollution Research, 2022)

A time series forecasting analysis of overall and sector-based natural gas demand: a developing South Asian economy case - Anwar Hussain; Junaid Alam Memon; Muntasir Murshed; Md Shabbir Alam; Usman Mehmood; Mohammad Noor Alam; Muhammad Rahman; Umar Hayat (Environmental Science and Pollution Research, 2022)

Spatial green growth in China: exploring the positive role of investment in the treatment of industrial pollution - Muhammad Imran; Naveed Hayat; Muhammad Ali Saeed; Abdul Sattar; Salman Wahab (Environmental Science and Pollution Research, 2022)

Impact of Climate Change on Dryland Agricultural Systems: A Review of Current Status, Potentials, and Further Work Need - Mukhtar Ahmed; Rifat Hayat; Munir Ahmad; Mahmood ul-Hassan; Ahmed M. S. Kheir; Fayyaz ul-Hassan; Muhammad Habib ur-Rehman; Farid Asif Shaheen; Muhammad Ali Raza; Shakeel Ahmad (International Journal of Plant Production, 2022)

Application of CSM-CANEGRO Model for Climate Change Impact Assessment and Adaptation for Sugarcane in Semi-arid Environment of Southern Punjab, Pakistan - Muhammad Nadeem; Muhammad Nazer Khan; Ghulam Abbas; Zartash Fatima; Pakeeza Iqbal; Mukhtar Ahmed; Muhammad Ali Raza; Abdul Rehman; Ehsan Ul Haq; Akbar Hayat; Muhammad Ali; Shakeel Ahmad (International Journal of Plant Production, 2022)

Screening of Rice Cultivars for Nitrogen Use Efficiency and Yield Stability under Varying Nitrogen Levels - Weilu Wang; Liying Huang; Guanglong Zhu; Hao Zhang; Zhiqin Wang; Muhammad Adnan; Shah Saud; Zafar Hayat; Shah Fahad (Journal of Plant Growth Regulation, 2022)

RETRACTED ARTICLE: Novel acetamide derivatives of 2-aminobenzimidazole prevent inflammatory arthritis in rats via suppression of pro-inflammatory mediators - Aymun Madni Zubair; Muhammad Nasir Hayat Malik; Waqas Younis; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Alamgeer Yuchi; Muhammad Naveed Mushtaq; Romeeza Tahir; Muhammad Bilal Sarwar; Muhammad Roman; Ayaz Ali Khan; et al. (Inflammopharmacology, 2022)

Pharmacological evaluation of anti-arthritic potential of terpinen-4-ol using in vitro and in vivo assays - Sania Aslam; Waqas Younis; Muhammad Nasir Hayat Malik; Shah Jahan; Alamgeer; Ambreen Malik Uttra; Muhammad Usman Munir; Muhammad Roman (Inflammopharmacology, 2022)

Exogenous melatonin mitigates chromium toxicity in maize seedlings by modulating antioxidant system and suppresses chromium uptake and oxidative stress - Zaffar Malik; Sobia Afzal; Muhammad Dawood; Ghulam Hassan Abbasi; Muhammad Imran Khan; Muhammad Kamran; Mostafa Zhran; Malik Tahir Hayat; Muhammad Naveed Aslam; Muhammad Rafay (Environmental Geochemistry and Health, 2022)

Integrated management of Striga gesnerioides in cowpea using resistant varieties, improved crop nutrition and rhizobium inoculants - Wajiha M. Abdullahi; Mahamadi Dianda; Ousmane Boukar; Ibnou Dieng; Gaya S. Mohammed; Nouhoun Belko; Abou Togola; Hayat Muhammad; Fred Kanampiu; Ken E. Giller; Bernard Vanlauwe (Plant and Soil, 2022)
Background Cowpea is a grain legume of major importance in sub-Saharan Africa where it is cultivated by smallholder farmers on poor soils and production is often constrained by the parasitic weed Striga gesnerioides . Method Experiments were conducted to assess the potential of rhizobium inoculation to mitigate Striga infection and increase cowpea productivity. We infested soils with S. gesnerioides and assessed the impact of treatments combining cowpea genotypes and bradyrhizobium inoculation on Striga dynamics and cowpea yield. In total, 20 cowpea genotypes were included, of which nine were resistant to Striga and 11 were susceptible. In the first experiment these were factorially combined with three inoculation options (two bradyrhizobium strains USDA3384 and IRJ2180A, and uninoculated control) in a screen-house using potted sterile soils. Second, the same trial was repeated in the field with basal phosphorus applied at sowing and a fourth treatment of fertilizer-N (urea) included testing whether N was limiting cowpea growth. The field trial also included a separate treatment with no input that served as a negative check. Result Significant genotype x treatment interactions were observed in nodule counts, Striga attachment, emergence, and cowpea shoot growth in the screen-house. There were few nodules across all cowpea lines. Striga counts were the lowest for resistant varieties with no emerged plants. Rhizobial inoculants depressed Striga counts with consistent differences across cowpea genotypes. Inoculation with IRJ2180A performed the best against Striga attachment in resistant genotypes, and against Striga emergence in susceptible genotypes. In the field trial, cowpea grown without inputs had the least number of nodules. The genotype x treatment interaction was significant: resistant cowpea genotypes were free of emerged Striga while there was much more Striga emergence without input addition with susceptible genotypes. A significant genotype x treatment interaction was observed on cowpea grain yield. Yield response to inoculation was clearest with resistant genotypes inoculated with the strain IRJ2180A. Conclusion The integrated use of Striga -resistant cowpea lines, basal phosphorus fertilizer and elite bradyrhizobium inoculants is a promising approach to mitigate Striga infection and increase cowpea productivity.

Production of bimodal molecular weight levan by a Lactobacillus reuteri isolate from fish gut - Waqar Ahmad; Anam Nasir; Fazal Sattar; Iram Ashfaq; Ming-Hsu Chen; Azam Hayat; Mujaddad ur Rehman; Sainan Zhao; Shazia Khaliq; Muhammad Afzal Ghauri; Munir Ahmad Anwar (Folia Microbiologica, 2022)

Re-investigating the nexuses of renewable energy, natural resources and transport services: a roadmap towards sustainable development - Syed Abdul Rehman Khan; Muhammad Umer Quddoos; Muhammad Hanif Akhtar; Amir Rafique; Mustansar Hayat; Saqib Gulzar; Zhang Yu (Environmental Science and Pollution Research, 2022)

Bio-diesel production of sunflower through sulphur management in a semi-arid subtropical environment - Athar Mahmood; Masood Iqbal Awan; Sana Sadaf; Ahmed Mukhtar; Xiukang Wang; Sajid Fiaz; Sher Aslam Khan; Habib Ali; Faran Muhammad; Zafar Hayat; Farhana Gul; Shah Fahad (Environmental Science and Pollution Research, 2022)

Exploring factors of the sustainable supply chain in the post-COVID-19 pandemic: SWARA approach - Khizar Hayat; Zhu JianJun; Sharafat Ali; Muhammad Adeel Khan (Environmental Science and Pollution Research, 2021)

Correction to: Health risk assessment of hexachlorocyclohexane in soil, water and plants in the agricultural area of Potohar region, Punjab, Pakistan - Talat Ara; Waqar-Un Nisa; Rukhsanda Aziz; Muhammad Tariq Rafiq; Rafaqat Ali Gill; Malik Tahir Hayat; Uzma Afridi (Environmental Geochemistry and Health, 2021)

Health risk assessment of hexachlorocyclohexane in soil, water and plants in the agricultural area of Potohar region, Punjab, Pakistan - Talat Ara; Waqar-Un Nisa; Rukhsanda Aziz; Muhammad Tariq Rafiq; Rafaqat Ali Gill; Malik Tahir Hayat; Uzma Afridi (Environmental Geochemistry and Health, 2021)

Occupational health impacts of transport industry: collagen degrader, blood lead, and respiratory illnesses - Waheed Anjum; Nadia Riaz; Muhammad Saqib; Malik Tahir Hayat; Zahid Ullah; Qaisar Mahmood (Arabian Journal of Geosciences, 2021)

Carbon-Based Slow-Release Fertilizers for Efficient Nutrient Management: Synthesis, Applications, and Future Research Needs - Muhammad Rashid; Qaiser Hussain; Khalid Saifullah Khan; Mohammad I. Alwabel; Rifat Hayat; Muhammad Akmal; Shahzada Sohail Ijaz; Sarosh Alvi; Obaid-ur-Rehman (Journal of Soil Science and Plant Nutrition, 2021)

Drought Tolerance Strategies in Plants: A Mechanistic Approach - Muhammad Ilyas; Mohammad Nisar; Nadeem Khan; Ali Hazrat; Aamir Hamid Khan; Kashif Hayat; Shah Fahad; Aziz Khan; Abid Ullah (Journal of Plant Growth Regulation, 2021)

Microfacies analysis and reservoir evaluation based on diagenetic features and log analysis of the Nammal Formation, Western and Central Salt Range, Upper Indus Basin, Pakistan - Jabir Hussain; Tahseenullah Khan; Birkhez Aslam Shami; Muhammad Zafar; Tassawar Hayat (Arabian Journal of Geosciences, 2021)

Artemisia chamaemelifolia Vill: a rare species of genus Artemisia (Asteraceae-Anthemideae) now present in the northeast (Gilgit-Baltistan) region of Pakistan - Adil Hussain; Muhammad Qasim Hayat; Syed Ali Imran Bokhari (Biologia, 2021)

Biological and phytochemical studies on Capparis decidua (Forssk) Edgew from Cholistan desert - Shazia Anjum; Muhammad Asif; Kashaf Zia; Bakhat Jahan; Muhammad Ashraf; Shafqat Hussain; Muhammad Qasim Hayat; Muhammad Raza Shah; Muhammad Nawaz Tahir (Natural Product Research, 2020)

Erratum to: Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018 - Jawaria Gul; Sher Muhammad; Shi-yin Liu; Siddique Ullah; Shakeel Ahmad; Huma Hayat; Adnan Ahmad Tahir (Journal of Mountain Science, 2020)
The article Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018, written by Jawaria GUL, Sher MUHAMMAD, LIU Shi-yin, Siddique ULLAH, Shakeel AHMAD, Huma HAYAT and Adnan Ahmad TAHIR, was originally published Online First without Open Access. After publication in volume 17, issue 3, page 572-587, the author decided to opt for Open Choice and to make the article an Open Access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2020 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits use, duplication, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made. The original version of this article has been revised due to a retrospective Open Access order.

Aluminium oxide nanoparticles inhibit EPS production, adhesion and biofilm formation by multidrug resistant Acinetobacter baumannii - Saima Muzammil; Mohsin Khurshid; Iqra Nawaz; Muhammad Hussnain Siddique; Muhammad Zubair; Muhammad Atif Nisar; Muhammad Imran; Sumreen Hayat (Biofouling, 2020)

Characterization of a novel cotton MYB gene, GhMYB108-like responsive to abiotic stresses - Abid Ullah; Muhammad Tahir Ul Qamar; Mohammad Nisar; Ali Hazrat; Gul Rahim; Aamir Hamid Khan; Kashif Hayat; Saeed Ahmed; Waqar Ali; Aziz khan; Xiyan Yang (Molecular Biology Reports, 2020)

Integrated assessment of extreme climate and landuse change impact on sediment yield in a mountainous transboundary watershed of India and Pakistan - Muhammad Babur; Sangam Shrestha; Binod Bhatta; Avishek Datta; Hayat Ullah (Journal of Mountain Science, 2020)

Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018 - Jawaria Gul; Sher Muhammad; Shi-yin Liu; Siddique Ullah; Shakeel Ahmad; Huma Hayat; Adnan Ahmad Tahir (Journal of Mountain Science, 2020)
Glaciers in the northern Pakistan are a distinctive source of freshwater for the irrigation, drinking and industrial water supplies of the people living in those regions and downstream. These glaciers are under a direct global warming impact as indicated in many previous studies. In this study, we estimated the glacier dynamics in terms of Equilibrium Line Altitude (ELA), mass balance and the snout position variation using remote sensing data between 2001 and 2018. Six glaciers, having area ≥ 20 km 2 each, situated in the Chitral region (Hindukush Mountains) were investigated in this study. Digital Elevation Model (DEM) and available cloud-free continuous series of Landsat and Sentinel the entire study area was a retreat of -231 ± 140 m. No obvious relationship was found between the glacier variation trends and the available gauged climatic data possibly due to the presence of debris cover in ablation zones of all the studied glaciers which provides insulation and reduces the immediate climatic effects.

Revealing heterogeneous causal links among financial development, construction industry, energy use, and environmental quality across development levels - Munir Ahmad; Gul Jabeen; Muhammad Khizar Hayat; Rana Ejaz Ali Khan; Shoaib Qamar (Environmental Science and Pollution Research, 2020)

Isolation and functional characterization of an Ethylene Response Factor (RhERF092) from rose (Rosa hybrida) - Muhammad Ali Khan; Muhammad Imtiaz; Adil Hussain; Fazal Jalal; Sikandar Hayat; Sayed Hussain; Fazal Said; Mehboob Alam; Rabia Amir (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Correction to: Characterization, the Antioxidant and Antimicrobial Activity of Exopolysaccharide Isolated from Poultry Origin Lactobacilli - Muhammad Shahid Riaz Rajoka; Hafiza Mahreen Mehwish; Hafiz Fakhar Hayat; Nazim Hussain; Sobia Sarwar; Humaira Aslam; Ahmad Nadeem; Junling Shi (Probiotics and Antimicrobial Proteins, 2019)

Characterization, the Antioxidant and Antimicrobial Activity of Exopolysaccharide Isolated from Poultry Origin Lactobacilli - Muhammad Shahid Riaz Rajoka; Hafiza Mahreen Mehwish; Hafiz Fakhar Hayat; Nazim Hussain; Sobia Sarwar; Humaira Aslam; Ahmad Nadeem; Junling Shi (Probiotics and Antimicrobial Proteins, 2019)

Effects of biochar and NPK on soil microbial biomass and enzyme activity during 2 years of application in the arid region - Muhammad Azeem; Rifat Hayat; Qaiser Hussain; Muhammad Ibrahim Tahir; Muhammad Imran; Zafar Abbas; Muhammad Sajid; Abdul Latif; Muhammad Irfan (Arabian Journal of Geosciences, 2019)

Glucanolytic Rhizobacteria Produce Antifungal Metabolites and Elicit ROS Scavenging System in Sugarcane - Muhammad Atif Zia; Humaira Yasmin; Faluk Shair; Zahra Jabeen; Saqib Mumtaz; Zafar Hayat; Syed Zia ul Husnain Shah; Shahid Afghan; Fauzia Yusuf Hafeez; Muhammad Nadeem Hassan (Sugar Tech, 2019)

Bait attractants based on artificial fruit-essence for trapping and monitoring Drosophila suzukii (Diptera: Drosophilidae) females in Peshawar-Pakistan - Muhammad Shehzad Khan; Farman Ullah; Hayat Badshah; Bashir Ahmad; Inayat Ali Shahjehan; Paul-André Calatayud (Phytoparasitica, 2019)

iNuc-ext-PseTNC: an efficient ensemble model for identification of nucleosome positioning by extending the concept of Chou’s PseAAC to pseudo-tri-nucleotide composition - Muhammad Tahir; Maqsood Hayat; Sher Afzal Khan (Molecular Genetics and Genomics, 2019)

Response of soil microbial biomass and enzymatic activity to biochar amendment in the organic carbon deficient arid soil: a 2-year field study - Muhammad Irfan; Qaiser Hussain; Khalid Saifullah Khan; Muhammad Akmal; Shahzada Sohail Ijaz; Rifat Hayat; Azeem Khalid; Muhammad Azeem; Muhammad Rashid (Arabian Journal of Geosciences, 2019)

Riverine flood assessment in Jhang district in connection with ENSO and summer monsoon rainfall over Upper Indus Basin for 2010 - Bushra Khalid; Bueh Cholaw; Débora Souza Alvim; Shumaila Javeed; Junaid Aziz Khan; Muhammad Asif Javed; Azmat Hayat Khan (Natural Hazards, 2018)

TNFα-induced DLK activation contributes to apoptosis in the beta-cell line HIT - Svenja Börchers; Rohollah Babaei; Catarina Klimpel; Jorge Duque Escobar; Sabine Schröder; Roland Blume; Muhammad Nasir Hayat Malik; Elke Oetjen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Prediction of Protein Submitochondrial Locations by Incorporating Dipeptide Composition into Chou’s General Pseudo Amino Acid Composition - Khurshid Ahmad; Muhammad Waris; Maqsood Hayat (The Journal of Membrane Biology, 2016)

Psychrophilic and psychrotrophic fungi: a comprehensive review - Noor Hassan; Muhammad Rafiq; Muhammad Hayat; Aamer Ali Shah; Fariha Hasan (Reviews in Environmental Science and Bio/Technology, 2016)

iRSpot-GAEnsC: identifing recombination spots via ensemble classifier and extending the concept of Chou’s PseAAC to formulate DNA samples - Muhammad Kabir; Maqsood Hayat (Molecular Genetics and Genomics, 2016)

Alleviation of chromium toxicity by glycinebetaine is related to elevated antioxidant enzymes and suppressed chromium uptake and oxidative stress in wheat (Triticum aestivum L.) - Shafaqat Ali; Aaifa Chaudhary; Muhammad Rizwan; Hafiza Tania Anwar; Muhammad Adrees; Mujahid Farid; Muhammad Kashif Irshad; Tahir Hayat; Shakeel Ahmad Anjum (Environmental Science and Pollution Research, 2015)

EDTA enhanced plant growth, antioxidant defense system, and phytoextraction of copper by Brassica napus L. - Ume Habiba; Shafaqat Ali; Mujahid Farid; Muhammad Bilal Shakoor; Muhammad Rizwan; Muhammad Ibrahim; Ghulam Hasan Abbasi; Tahir Hayat; Basharat Ali (Environmental Science and Pollution Research, 2015)

Erratum to: Sphingobacterium pakistanensis sp. nov., a novel plant growth promoting rhizobacteria isolated from rhizosphere of Vigna mungo - Iftikhar Ahmed; Muhammad Ehsan; Yeseul Sin; Jayoung Paek; Nauman Khalid; Rifat Hayat; Young H. Chang (Antonie van Leeuwenhoek, 2014)

Sphingobacterium pakistanensis sp. nov., a novel plant growth promoting rhizobacteria isolated from rhizosphere of Vigna mungo - Iftikhar Ahmed; Muhammad Ehsan; Yeseul Sin; Jayoung Paek; Nauman Khalid; Rifat Hayat; Young H. Chang (Antonie van Leeuwenhoek, 2014)

Serum Electrolyte and Mineral Variations During Pregnancy and Lactation in Nili-Ravi Buffalo - M. Saleem Akhtar; Abdul Asim Farooq; Syed Aun Muhammad; Laeeq Akbar Lodhi; C. Sikandar Hayat; M. Mushtaq Aziz (Biological Trace Element Research, 2010)

A convenient iodination method for alcohols using cesium iodide/methanesulfonic acid and its comparison using cesium iodide/ p -toluenesulfonic acid or cesium iodide/aluminium chloride - Khalid Mohammed Khan; Shahnaz Perveen; Safdar Hayat; Muhammad Ali; Wolfgang Voelter (Natural Product Research, 2008)

Series solution for steady flow of a third grade fluid through porous space - Muhammad Sajid; Tasawar Hayat (Transport in Porous Media, 2008)